EFFECTIVENESS OF CONSERVATIVE TREATMENT FOR CHRONIC PERIODONTITIS IN CHILDREN USING CALCIUM-CONTAINING MEDICATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The treatment of chronic apical periodontitis in multi-rooted permanent teeth with fully developed roots in children and adolescents represents a significant issue in dentistry, particularly in the presence of destructive changes in bone tissue. The aim of the study was to evaluate the effectiveness of conservative therapy methods using calcium-containing medications. Two clinical observations were conducted: in the first case, single-stage root canal filling was performed for granulating periodontitis without signs of exudation; in the second, temporary root canal obturation was applied using a combined calcium-containing medication for granulomatous periodontitis with signs of exudation. The methods included clinical examination, radiographic monitoring, and long-term follow-up of the patients. The results demonstrated complete restoration of bone structure and elimination of inflammatory symptoms. The conclusions confirm that the use of calcium-containing medications is effective in treating destructive forms of apical periodontitis in children and adolescents. The novelty of the study lies in a comprehensive approach that combines various treatment regimens depending on the clinical form of the disease, ensuring tissue regeneration and preservation of tooth functionality. The findings are recommended for use in pediatric dental practice.